PENGARUH ALELOKIMIA EKSTRAK TANAMAN PADI (Oryza sativa L. Var. IR64) TERHADAP PERKECAMBAHAN DAN PERKEMBANGAN KECAMBAH KEDELAI (Glycine max L.) - Mahayaning, Fitrian Agna; Darmanti, Sri; Nurchayati, Yulita (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2015)
The aim of this research is to know the allelochemicals effect of rice var. IR 64 residues extract on germination and growth soybean var. Grobogan seedling. This experiment uses completely randomized factorial design (3x5). The fist factors is extract resources (root, straw, and hull) and secont factor is level concentration extrac (0%, 25%, 50%, 75%, dan 100%) with 5 replicates. Data analysed using ANOVA and DMRT.The results showed that allelochemicals from residue of rice IR 64 extract inhibit the germination and growth soybean var. Grobogan seedling, the higher concentration of the treatment the greater inhibition. Inhibition most likely caused by a hull rice extract. Keywords: Glycine max, Oryza sativa, allelochemical, phenol